Effects of phase ratio and velocity conversion coefficient on the performance of the triple jump - Liu, H.; Yu, B. (Journal of Sports Sciences, 2012)
Phase ratio is a measure of effort distribution in the triple jump. Hop-dominant, balanced, and jump-dominant techniques were three triple jump techniques defined based on phase ratio. The purpose of this study was to determine the effect of the phase ratio on the performance of the triple jump. Three-dimensional kinematic data of 13 elite male triple jumpers were obtained during a competition. Computer simulations were performed using a biomechanical model of the triple jump to optimise the phase ratio for the longest actual distance using each of the three techniques for a given athlete with altered velocity conversion coefficients. The velocity conversion coefficient affected which technique achieved the longest actual distance. The actual distance obtained using the hop-dominant technique was significantly longer than that obtained using the other two techniques (P = 0.007, P = 0.001) when the velocity coefficient was between 0.35 and 0.55. The actual distance obtained using the jump-dominant technique was significantly longer than that obtained using the other two techniques (P = 0.001, P = 0.002) when the velocity coefficient was between 0.80 and 1.30. No consistent optimum technique across participants and no significant difference in performance among the three techniques were found (P > 0.524) when the velocity coefficient was between 0.60 and 0.75.